Parents' and speech and language pathologists' attitudes toward preschool children with speech and language disorders - Dulčić, Adinda (Array, 2018)
The objective of this study was to analyze speech and language pathologists' (SLPs) and parents' attitudes toward the behavior of children with speech and language disorders. The research was conducted in the SUVAG Polyclinic kindergarten. Examinees were parents and speech and language pathologists who on daily basis encourage language development of twenty-two children with speech and language disorders. The study examined to what extent SLPs and parents agree in the assessment of child’s attention, impulsiveness and activity. A questionnaire developed solely for the purpose of this research was administered. It gathered information regarding child’s attention, impulsiveness and activity. Results have shown that parents and speech and language pathologists differed in their attitudes toward the behavior of children with speech and language disorders.